Pendidikan Islam Transformatif Perspektif Maulana Syaikh TGKH Muhammad Zainuddin Abdul Majid di Nusa Tenggara Barat - Lalu Abdurrahman Wahid; Finna Baity Janah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Reform in the realm of education in the perspective of Islamic education reformers is seen as an effective way in the process of Islamization in the archipelago and a strategic step in shaping the Islamic view of society. This article aims to analyze the transformation and progression of Islamic education promoted by TGKH. Muhammad Zainuddin Abdul Majid. This research was carried out in accordance with the principles of qualitative research using the library research. The result of this research is that the transformative Islamic education initiated by TGKH. Muhammad Zainuddin Abdul Majid by reforming several aspects of Islamic education was seen as very relevant to the condition of the people of Lombok at that time who were still in a state of ignorance due to pressure from the Dutch colonials. Renewal in the realm of Islamic education was seen as a strategic step in elevating the dignity of society at that time. Updates carried out by TGKH. Muhammad Zainuddin Abdul Majid carried out on aspects of learning materials, Islamic education goals and methods of Islamic education. From several aspects of the renewal, it is seen as relevant in the current era which is all technological and the demands of contemporary education learning today. students as figures of the Muslim generation are equipped to survive with the demands of the times while still being based on noble character and a foundation of religious knowledge that is capable, militant, has a patriotic spirit and high nationalism.